Fire Effects on Understory Forest Regeneration in Southern Amazonia - Prestes, Nayane Cristina Candida dos Santos; Massi, Klécia Gili; Silva, Estevão Alves; Nogueira, Denis Silva; de Oliveira, Edmar Almeida; Freitag, Renata; Marimon, Beatriz Schwantes; Marimon-Junior, Ben Hur; Keller, Michael; Feldpausch, Ted R. (Frontiers in Forests and Global Change, 2020)
Fire in tropical forests increases tree mortality, degrades forest structure and reduces carbon stocks. Currently, there are large gaps in understanding how fire affects understory forest structure and composition, interactions with fire recurrence, and long-term impacts. Understanding these changes is critical to evaluate the present and future response of tropical forests to fire. We studied post-fire changes in understory regeneration in forests in Mato Grosso State, southern Amazonia, Brazil, aiming to answer the following questions: (i) does forest structure (basal area) and tree community composition vary with fire frequency and time since the last fire? (ii) does the response differ among strata (e.g., sapling, larger trees)? (iii) are changes in diversity associated with changes in forest structure? We surveyed trees and lianas in previously structurally intact forests that underwent selective logging, followed by different fire histories, including 5 and 16 years after once-burned, 5 years after three times burned, and unburned (control). Overall, species composition (abundance, richness and number of families) and diversity were highest for the unburned treatment and lowest for the recurrent burned areas. Fire frequency negatively affected plant structure and basal area; plants from the most frequently burned areas had more than 50% less basal area than unburned sites. Richness was positively related to basal area in the three times burned sites and in the sixteen years regenerating site for all strata. Our results demonstrate the negative influence of frequent fires on both the composition and structure of small trees in Amazonian forest. These changes to the cohort of small-sized trees may persist and have long-term impacts on forest structure, affecting the capacity and direction of forest recovery. With wildfire widespread across the region and increasing in frequency, fire may negatively affect tree diversity in remaining selectively logged forests and affect regional carbon cycling with consequences for the global vegetation carbon sink.